Safety assessment of the analyzed jewelry concerning nickel migration on the Serbian market - Stanković, Marija; Stanisavljev, Ana; Djordjević, Marija; Janković, Milica; Piperin, Vesna (Archives of Pharmacy, 2022)
The aim of this work was to assess the safety of jewelry concerning nickel migration, having in mind that this metal causes allergic contact dermatitis. The safety assessment was in line with REACH Directive, regulated by the Rulebook on Restrictions and Prohibitions on Production, Marketing and Use of Chemicals. The reference method for testing the release of nickel from all components that are placed in pierced parts of the human body and articles intended to come into direct and prolonged contact with the skin is defined by the standard SRPS EN 1811:2016. Test involves pre-immersing the sample in a migratory sweat solution (pH of 6.5 ± 0.05) for 7 days at 30 0C. Nickel content in migratory solution of sweat is determined by ICP-OES technique. Maximum permitted amount of nickel released from products placed in pierced parts of human body must not exceed 0.2 µg/cm2 per week, and in products intended for direct and prolonged contact with skin 0.5 µg/cm2 per week. Among 200 analyzed jewelry samples in the last 5 years, it was found that 10% did not satisfy the safety criteria concerning nickel migration. Most of the analyzed jewelry samples met the safety criteria set by the national regulations and standards. However, it is worrying that there is still a significant number of samples that do not meet this criteria, knowing that criteria for nickel migration from jewelry was set on 30th June 1994 by the amendment to Directive76/769/EEC, which precedes REACH Directive.